Inactivated mycobacterium paragordonae delivered via microneedle patches as a novel tuberculosis booster vaccine - Moonsu Lee; Dohyeon Jeong; Kiyoung Yoon; Juyoung Jin; Yong Woo Back; In-Taek Jang; Hwa-Jung Kim; Bum-Joon Kim; Sung Min Bae (Human Vaccines & Immunotherapeutics)
Tuberculosis (TB) remains a significant global health challenge with approximately 8.2 million new cases reported in 2023, despite the century-old Bacillus Calmette-Guérin (BCG) vaccine. BCG’s protective efficacy diminishes over time, especially against pulmonary TB in adults. This study evaluates ethanol-inactivated Mycobacterium paragordonae (M.pg) delivered via Microneedle Array Patches (MAPs) as a novel booster strategy to enhance BCG vaccination efficacy. Various inactivation methods including heat treatment, formalin, and ethanol were compared, with ethanol-inactivated M.pg selected for optimal preservation of morphology and immunologically significant proteins. MAPs were fabricated using the droplet extension technique (DEN). Immunological assessment was conducted in a mouse model receiving either BCG alone or BCG followed by one or two administrations of inactivated M.pg MAP. Protective efficacy was evaluated through M. tuberculosis H37Rv challenge. Ethanol inactivation uniquely preserved morphology and maintained protein integrity, particularly Ag85B. Two administrations of inactivated M.pg following BCG priming significantly enhanced protective immune responses compared to BCG alone, inducing strong Th1-polarized immunity characterized by elevated IFN-γ, TNF-α, and IL-2 production in both CD4+ and CD8+ T cells. This vaccination strategy effectively generated effector memory T cells in lung and spleen, contributing to significant reduction in bacterial burden following challenge, with the BCG+Inactivated M.pg2nd group demonstrating the greatest reduction. Inactivated M.pg delivered via microneedle patches represents an effective booster strategy for enhancing BCG-induced protection against tuberculosis, with a two-dose schedule demonstrating optimal efficacy. This approach combines the safety advantages of an inactivated vaccine with the practical benefits of MAPs, addressing key limitations of tuberculosis vaccination strategies.